Mycobacteriophage Ms6 : exploring the involvement of Gp1 on LysA export - Martins, Francisco André de Lemos (2015)
Tese de mestrado, Ciências Biofarmacêuticas, Universidade de Lisboa, Faculdade de Farmácia, 2014